Analisis Perbedaan Materi Pokok Pembelajaran Sejarah Peradaban Islam Pada Kurikulum 2013 dan Kurikulum Prototipe 2022 - Basuki (Universitas Yudharta Pasuruan, 2022)
The burden of learning achievement in the history of Islamic civilization in the subjects of Islamic Religious Education and Character Education (PAI and BP) in the 2013 curriculum is quite heavy. Because learning achievement must reach four dimensions of achievement indicators (spiritual attitudes, social attitudes, knowledge, skills), this condition became one of the backgrounds for implementing the 2022 prototype curriculum. This study aims to identify and analyze the burden of learning achievement of the history of Islamic civilization in PAI and BP subjects in the 2013 and 2022 prototype curricula. The research library with the primary data sources being